Фiзичнi властивостi кремнiєвих сенсорних структур з фотоелектричним принципом перетворення на основi “глибокого” p–n-переходу - Kozinetz, A. V.; Litvinenko, S. V.; Skryshevsky, V. A. (Publishing house "Academperiodika", 2018)
A capability to produce effective sensor structures on the basis of “deep”silicon junction has been substantiated. If the incident light is strongly absorbed by this junction, the photocurrent through it is shown to substantially depend on the recombination characteristics and the charge state of the illuminated surface, provided that the junction parameters are optimal. The depth of the illuminated region is demonstrated to exceed the diffusion length of minority charge carriers. It is found that the larger diffusion length of minority charge carriers corresponds to stronger changes of the photocurrent generated by the illuminated surface area. A possibility to transform the junction from a photodetector into an effective chemical sensor is verified by numerical calculations. The physical mechanisms relating the changes in the effective surface recombination rate and the absorption of polar molecules are discussed. The sensor properties of suggested silicon junctions are analyzed for a number of analytes. Their suitability for the creation of selective chemical sensors (electronic noses) is demonstrated experimentally.